2002
DOI: 10.1891/1058-1243.11.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth Education Outcomes: An Integrative Review of the Literature

Abstract: Abstractcriteria. The literature demonstrated inconclusive evidence regarding the effectiveness of childbirth education. None of the studies used a theoretical framework that proposed multiple factors, as opposed to childbirth education alone, that impact the outcomes. Health-focused versus illness-focused outcomes were also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 3 publications
0
36
0
2
Order By: Relevance
“…All of the participants were married, Caucasian, spoke English, and had completed at least some college. Although homogeneous, the sample was characteristic of the childbirth education attendees reported in the literature (Koehn, 2002;Nichols & Gennaro, 2000;Sims-Jones et al, 1998;Spiby et al, 2003;Stamler, 1998) and in the researcher's setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the participants were married, Caucasian, spoke English, and had completed at least some college. Although homogeneous, the sample was characteristic of the childbirth education attendees reported in the literature (Koehn, 2002;Nichols & Gennaro, 2000;Sims-Jones et al, 1998;Spiby et al, 2003;Stamler, 1998) and in the researcher's setting.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, childbirth education's popularity continues, is often considered a standard of care (Enkin, Keirse, Renfrew, & Neilson, 1999), and is included as an objective in Healthy People 2010 (U.S. Department of Health and Human Services, 2000). Nevertheless, an abundance of childbirth education research has not demonstrated strong evidence to support how participation in classes affects the experience of childbirth (Gagnon, 2004;Humenick, 2000;Jones, 1983;Koehn, 2002;Spiby, Slade, Escott, Henderson, & Fraser, 2003). Further findings from the literature indicate that classes continue to be structured from the perspective of the educator rather than from the assessed needs of the participants (Enkin et al, 1999;Nichols & Gennaro, 2000;Nolan, 1997Nolan, , 1999.…”
mentioning
confidence: 99%
“…In addition, existing studies measured numerous different outcomes, which makes it difficult to compare these studies and draw valid conclusions about the benefits of childbirth education (Koehn, 2002). When comparing specific models of childbirth education (CenteringPregnancy) to standard prenatal care using random assignment of women, CenteringPregnancy is associated with better outcomes.…”
Section: Childbirth Education and Obstetric Outcomesmentioning
confidence: 99%
“…Nevertheless, the review of publications on antenatal classes conducted by M.L. Koehn, and the guidelines of the National Institute for Health and Clinical Excellence, indicate that women participating in this form of preparation for parenthood had a better knowledge on responsibility for health than women who did not participate [22,23].…”
Section: Discussionmentioning
confidence: 99%